Influence of zein on viscoelastic properties and gluten network development during dough formation - Tingting Hong; Zhiwen Tan; Dan Xu; Yamei Jin; Fengfeng Wu; Guidong Huang; Xianfeng Zhong; Junhui Zhang; Xueming Xu (Food Chemistry: X)
This study investigated the effects of zein addition on the viscoelastic properties and gluten network of wheat dough. Results from Mixolab and dynamic rheometer showed that 2–3 % zein enhanced dough softness without affecting development time, stability, or creep recovery, while reducing pasting viscosity. Zein increased free water mobility, which decreased dough rigidity and facilitated deformation. Dough with 3 % zein showed a 26.50 % increase in free water relaxation time (T23). SE-HPLC revealed reduced gluten aggregation, increasing SDS-soluble polymeric and monomeric proteins and free sulfhydryl (SH) groups by 20 %. FTIR showed zein promoted antiparallel β-sheets and decreased β-sheet content. TGA indicated a 1.57 % increase in mass loss, and prolonged mixing lowered degradation temperature. CLSM confirmed zein weakened the gluten structure. These findings provided a better understanding of the interactions between zein and gluten in wheat dough, which could help optimize dough processing and improve product quality.